2016
DOI: 10.18632/oncotarget.7382
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of age-associated chronic degeneration of shoulder muscles

Abstract: Chronic muscle diseases are highly prevalent in the elderly causing severe mobility limitations, pain and frailty. The intrinsic molecular mechanisms are poorly understood due to multifactorial causes, slow progression with age and variations between individuals. Understanding the underlying molecular mechanisms could lead to new treatment options which are currently limited. Shoulder complaints are highly common in the elderly, and therefore, muscles of the shoulder's rotator cuff could be considered as a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…For this reason, we decided to study its effects on cultured muscle cells using a well-described experimental cellular model; mouse myoblast C 2 C 12 cells [ 30 ]. We analyzed the effect of ET-1 on some of the best studied aging-related aspects of myoblast biology, in particular on cellular senescence and ECM protein synthesis, since aging is associated with reductions in both muscle stem cell function and muscle regeneration potential, and with increased muscular fibrosis [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, we decided to study its effects on cultured muscle cells using a well-described experimental cellular model; mouse myoblast C 2 C 12 cells [ 30 ]. We analyzed the effect of ET-1 on some of the best studied aging-related aspects of myoblast biology, in particular on cellular senescence and ECM protein synthesis, since aging is associated with reductions in both muscle stem cell function and muscle regeneration potential, and with increased muscular fibrosis [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Senescence induced by ET-1 at vascular level has been involved in some pathologies [ 37 ], such as diabetes [ 38 ], varicosity [ 39 ] and thrombosis [ 40 ]. So, senescence induced by ET-1 at muscle level could be implicated in the development of fibrosis, exacerbating muscle damage, as the regenerative potential of skeletal muscle declines with age and this impairment is associated with an increase in tissue fibrosis [ 4 , 31 ]. Brack et al showed that muscle stem cells (satellite cells) from aged mice tend to convert from a myogenic to a fibrogenic lineage as they begin to proliferate and increase tissue fibrosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of gene expression patterns of rotator cuff muscle cells after a rotator cuff tear would be the first step and an important determinant in understanding the rotator cuff tear-related muscle changes and improving outcomes of rotator cuff repair surgery. Several studies have suggested various causes and mechanisms for muscle changes, such as atrophy and degeneration [9, 10, 2125]; however, despite this, much remains unknown. Progression of muscle degeneration, atrophy, and fatty infiltration is usually caused by abnormal signaling processes in muscle cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested various causes and mechanisms for muscle changes, such as atrophy and degeneration [9, 10, 2125]; however, despite this, much remains unknown. Progression of muscle degeneration, atrophy, and fatty infiltration is usually caused by abnormal signaling processes in muscle cells [25]. Abnormal muscle cell activities are the results of external stimuli, such as physical damage or aging, which lead to differentiation into fat cells or fibrous tissue and ultimately myocyte destruction (instead of normal myocyte differentiation) [26].…”
Section: Introductionmentioning
confidence: 99%